2021
DOI: 10.1097/md.0000000000025124
|View full text |Cite
|
Sign up to set email alerts
|

p-STAT3 expression in breast cancer correlates negatively with tumor size and HER2 status

Abstract: Although some studies have reported the expression and clinical significance of phosphorylated signal transducer and activator of transcription 3 (p-STAT3) in breast cancer tissues, it is still controversial whether p-STAT3 play a role in promoting or suppressing cancer. Here, we used immunohistochemistry analysis to explore expression of p-STAT3 in 407 cases of breast cancer, and analyzed the relationship between p-STAT3 expression and the clinicopathological characteristics and prognosis of breast cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…There is conflicting evidence regarding the prognostic value of STAT3 mRNA expression or immunostaining of phosphorylated STAT3 (phospho-STAT3), marking transcriptionally active STAT3. Positive phospho-STAT3 (Y705) expression is highest in TNBC, followed by luminal A and luminal B, with HER2-enriched tumors showing the lowest rate of phospho-STAT3 immunostaining [ 58 ], suggesting that phospho-STAT3 may be a hallmark of more aggressive breast cancer subtypes. Other studies and meta-analyses have positively correlated nuclear phospho-STAT3 localization to highly differentiated tumors, higher tumor grade and lymphatic metastasis, though there appears to be no relationship to overall survival outcomes [ 59 , 60 ].…”
Section: Activation Of Stat3 In the Breast Cancer Microenvironmentmentioning
confidence: 99%
“…There is conflicting evidence regarding the prognostic value of STAT3 mRNA expression or immunostaining of phosphorylated STAT3 (phospho-STAT3), marking transcriptionally active STAT3. Positive phospho-STAT3 (Y705) expression is highest in TNBC, followed by luminal A and luminal B, with HER2-enriched tumors showing the lowest rate of phospho-STAT3 immunostaining [ 58 ], suggesting that phospho-STAT3 may be a hallmark of more aggressive breast cancer subtypes. Other studies and meta-analyses have positively correlated nuclear phospho-STAT3 localization to highly differentiated tumors, higher tumor grade and lymphatic metastasis, though there appears to be no relationship to overall survival outcomes [ 59 , 60 ].…”
Section: Activation Of Stat3 In the Breast Cancer Microenvironmentmentioning
confidence: 99%
“…STAT1 and STAT3, are expressed in many, but not all, human breast tumors (Wang et al, 2021; Widschwendter et al, 2002). At the mRNA level, 64.2% of breast tumors in the METABRIC cohort display comparatively elevated STAT3 mRNA levels (Aleskandarany et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…At the mRNA level, 64.2% of breast tumors in the METABRIC cohort display comparatively elevated STAT3 mRNA levels (Aleskandarany et al, 2016). At the protein level, pSTAT3 is observed in ∼37.5% of TNBC patients, the highest of the three clinical subtypes (Wang et al, 2021). Although pSTAT1 has not been profiled as extensively in human breast tumors as pSTAT3, likely due to its known role as a tumor suppressor (Koromilas and Sexl, 2013), STAT1 activity has been detected using DNA binding assays and Western blot for pSTAT1 in a cohort of 73 breast cancer patients (Widschwendter et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these studies revealed that pSTAT3 overexpression in many patients has a poor prognostic value. ( 36 , 37 ) Other studies found that pSTAT3 overexpression is related to better prognosis and favorable outcomes, particularly in thyroid and breast carcinoma ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%